Effect of Road Markings on Speed Through Curves on Rural Roads: A Driving Simulator Study in Spain - Santiago Martin-Castresana; Diego Alvarez; Fabian Andrade-Cataño; Maria Castro (Infrastructures)
Traffic accidents remain a leading cause of mortality worldwide. In Spain, a total of 9666 accidents occurred on curves in 2023, highlighting the need for effective speed management strategies. This study analyses, using a driving simulator, the effectiveness of three low-cost traffic calming measures—checkerboard patterns, red peripheral transverse bars, and red coloured transverse bands—on vehicle speed through curves of varying radii and directions. Additionally, it examines the influence of driver characteristics (age, gender, and experience) and road geometric features (curve radius and direction) on driving behaviour. The simulated road included ten curves with radii ranging from 26 to 190 metres (operating speeds of 30–70 km/h) with traffic calming measures placed at the tangents before the curves. The sample consisted of 48 drivers. Men exhibited faster speeds than women, while younger drivers were faster than seniors. Increased driving experience (annual distances) correlated with higher speeds. Additionally, smaller radii resulted in lower speeds. Regarding the traffic calming measures, significant differences were found mainly where the road markings were placed (tangent) and in the initial phases of the curve. Checkerboard patterns performed better in curves with smaller radii. In contrast, red coloured transverse bands showed the best performance in larger radius curves.